An Analysis of Deixis in “Beauty and The Beast” Movie Script - Lorenza, Oktazsya Marjelina; Arsyad, Safnil; Kasmaini, Kasmaini (Journal of English Education and Teaching, 2024)
Deixis has an important role to build the communication process. This research aimed to find out the distribution of scenes, types of deixis are often found and distribution of deixis in all sections of Beauty and The Beast movie script by using Cruse theory (2000). This research used a descriptive qualitative method. The object of this study is Beauty and The Beast movie script by Stephen Chbosky and Evan Spiliotopoulos. Documentation and checklist were used in data collection. The results showed that the distribution of scenes in the Beauty and The Beast movie script are found in the orientation section, complication section, rising action section, turning point section and resolution section. Coda is not found in this movie. Then, person deixis, social deixis and spatial deixis are the most dominant deixis in Beauty and The Beast movie script. Finally, there were five types of deixis in the orientation section, complication section, rising action section, turning point section but there are only two types of deixis that are found in the resolution section in the Beauty and the Beast movie script. It is suggested that English teachers and students should be familiar with the types of deixis in the main section of the movie before using it for the teaching and learning process.